Elevation Effect on Acacia mangium Volume Estimation - Prem Kumar Selvarajan; Seca Gandaseca; Kamziah Abd. Kudus; Karuniawan Puji Wicaksono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The objective of this study was to examine the effects of four different elevations on Acacia mangium volume in Bintulu, Sarawak. A total of 60 felled trees of A. mangium were used to develop a volume equation by measuring the volume at four different classes of elevation. The study of stand volume estimation in Malaysian plantations, particularly in Bintulu, is sparse. To get the average cross-sectional area, the volume of each tree in each part of the felled trees was estimated using Smalian’s and Newton’s formulas. Four equations were developed in this study to predict the volume from the diameter and analyze the effect of elevation on tree volume. According to the regression analysis, there was a significant relationship between the volume and diameter for each slope steepness. The Very Slope site had the highest volume with an R² value of 0.948 for the model’s fit, which revealed that 94.8% of the data could be evaded. Volume estimation using the regression model can be used to determine and categorize according to its class of elevation, and there is an effect of elevation on standing volume. A. mangium has better growth performance in a very slope area in terms of tree volume compared to different elevations.